2011
DOI: 10.5770/cgj.v14i4.23
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D Dosing Regimen and Fall Prevention in Long-term Care Seniors

Abstract: IntroductionThe effectiveness of vitamin D in reducing falls among longterm care (LTC) seniors remains nonconclusive. We reviewed how vitamin D dosing regimen could affect rate of fall and number of fallers among LTC seniors.MethodsWe conducted a systematic literature review. Studies were selected by two independent reviewers based on study characteristics (age 75 or older), quality assessment (primary analysis randomized controlled trials), and outcome (rate of fall and number of fallers). Analyses of all tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Therefore, the result implies that community-dwelling patients may also benefit from taking vitamin D. Interestingly, subgroup analysis of the calculated daily dose >1,000 IU showed a trend of increased risk of fractures and falls, although it was insignificant. A recent study by Bolland et al [ 50 ] showed similar results, along with other meta-analyses [ 59 , 60 ], that intermittent vitamin D supplements raised fall risks. Although the reasons are not clear, intermittent supplements are usually given in high doses that are suspected to be the cause of increased fractures and falls.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, the result implies that community-dwelling patients may also benefit from taking vitamin D. Interestingly, subgroup analysis of the calculated daily dose >1,000 IU showed a trend of increased risk of fractures and falls, although it was insignificant. A recent study by Bolland et al [ 50 ] showed similar results, along with other meta-analyses [ 59 , 60 ], that intermittent vitamin D supplements raised fall risks. Although the reasons are not clear, intermittent supplements are usually given in high doses that are suspected to be the cause of increased fractures and falls.…”
Section: Discussionsupporting
confidence: 61%
“…Although the reasons are not clear, intermittent supplements are usually given in high doses that are suspected to be the cause of increased fractures and falls. Some studies suggested the U-shaped association between vitamin D and risk of fractures and falls, which could be mediated via the vitamin D receptor in the central nervous system [ 59 , 60 ]. Also, as the half-life of 25-hydroxyvitamin D (25(OH)D) is approximately 15 days, monthly or yearly intervals are likely to cause fluctuations that may lead to toxic levels of 25(OH)D in the blood [ 19 , 22 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of vitamin D deficiency and its role on muscle metabolism, etiology of muscle weakness, and increased risk of falls have been studied widely. [14][15][16][17][18] In this study, the difference of vitamin D levels between young and senior groups did not appear significant (27.15 versus 27.04 units/mL). One of the factors for this apparent lack of statistical difference might be the small number of patients.…”
Section: Discussionmentioning
confidence: 83%
“…Very high dose intermittent vitamin D supplementation (500 000 IU loading dose) has been associated with an increased risk of falls in one large trial [29]; the biological mechanism behind this finding is unclear, but might be due either to a blood pressurelowering effect negating any beneficial effects on orthostatic hypotension through other vascular pathways, or alternatively to differences in how levels of 25OHD and unhydroxylated vitamin D3 vary after bolus dosing compared to daily dosing. Vitamin D3 may be taken up (6) Other (5) BP out of range (3) Illness (7) Withdrew consent (7) End of recruitment (2) Expressed interest in study via news article: 22 and metabolized by non-renal and non-parathyroid tissues in a different way to circulating 25OHD [30]; this might provide the basis of a biological explanation for why a recent meta-analysis also suggested that daily supplementation may be more effective at preventing falls than intermittent dosing [31]. Another possibility is that different patient groups with orthostatic hypotension may respond in different ways.…”
Section: Discussionmentioning
confidence: 97%